Sol-gel Based Nanoceramic Materials: Preparation, Properties and Applications - Mishra, Ajay Kumar (Springer International Publishing : Imprint: Springer, 2017)
This book summarizes recent research and development in the field of nanostructured ceramics and their composites. It presents selected examples of ceramic materials with special electronic, catalytic and optical properties and exceptional mechanical characteristics. A special focus is on sol-gel based and organic-inorganic hybrid nanoceramic materials. The book highlights examples for preparation techniques including scale-up, properties of smart ceramic composites, and applications including e.g. waste water treatment, heavy metal removal, sensors, electronic devices and fuel cells. Recent challenges are addressed and potential solutions are suggested for these. This book hence addresses chemists, materials scientists, and engineers, working with nanoceramic materials and on their applications.